Rancang Bangun Alat Penghitung Bibit Ikan Mujair Otomatis Berbasis Mikrokontroler - Ulul Ilmi (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
Collection of fisheries and trade information it is very important to pay attention, reflecting on how to calculate fish seeds wich is manually what is done by taking fish seeds using doses (spoon) or using glass. In calculating farmers take fish seeds per five seeds per one measure. This method certainly requires a long time, especially if the number of fish seedlings to be purchased is large. In this final project, designed for automatic fish seed counting devices with Atmega328 microcontroller systems as a data processor, the photodiode sensor is the data sender and receiver, which is then displayed in LCD 16x2.So that we can get the addition of fish seeds automatically. The test result of the automatic fish binite counter will run if there is an object passing under the two LEDs that have a photodiode censor, then the data will be displayed on the LCD to show the number of fish passing.